(untitled) (Nexo Revista Científica, 2021)
The purpose of this study is to formulate a beet foam stable over time with the addition of Soy lecithin. Three concentrations of the foaming agent were tested (0.5, 1.0 and 1.5% w/V) using two methodologies (Suspension and Standing) in order to determine the foam’s stability. The viscocity of different dilutions were measured, and besides, the Ostwald maturation process was evaluated in the foam obtained. The beet juice formulation with 1.5% w/V soy lecithin had the highest viscosity, while the most effective procedure to maintain foam stability was the Standing method for no longer than 10 minutes. The beet foam was sensorially tested by experts giving the global category of good, highlighting the attractiveness it brings to traditional preparations.